Specialization and happiness: A US-Japan comparison - Kristen Schultz Lee; Hiroshi Ono (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
This paper examines the relationship between specialization and happiness in marriage in the U.S. and Japan. Our findings, based on the General Social Surveys in the U.S. and Japan, indicate both similarities and differences in the determinants of marital happiness in the two countries. In the U.S., the findings are mixed. Women in the U.S. are more likely to embrace the bargaining model where their happiness is determined by their own income. Men in the U.S. are more likely to support the specialization model; they are happier if their wives are not working or, alternatively, if they are financially dependent on their wives. In Japan, we find support for the specialization model, particularly in the case of women; they are happier if they are specialized in the household and they have a higher household income. Our research highlights how marital quality is affected by the institutional context and the normative environment.
Keywords: D13; J12; J16; 330; gender; family; marital happiness; specialization; bargaining; Arbeitsteilung; Geschlecht; Vergleich; Japan; USA; Zufriedenheit; Ehe